THE IMPACT OF TECHNOLOGY ON ISLAMIC PESANTREN EDUCATION AND THE LEARNING OUTCOMES OF SANTRI: NEW TRENDS AND POSSIBILITIES - Munir Tubagus; Haerudin; Apit Fathurohman; Adiyono; Aslan Aslan (CV. ADIBA AISHA AMIRA, 2023)
This paper explores the impact of technology on Islamic pesantren education and the learning outcomes of santri. The study highlights the emergence of new trends and possibilities in the integration of technology in pesantren education, including the use of online learning platforms, mobile applications, and social media. The paper also examines the potential benefits of technology in enhancing the pesantren education system, such as improved access to educational resources, enhanced communication, and new learning opportunities. Studies in this area typically use quantitative and qualitative research methods. Quantitative methods may include surveys and questionnaires to gather data on the use and impact of technology on pesantren education and student learning outcomes. Qualitative methods may include interviews and focus groups with pesantren educators, administrators, and students to better understand their experiences with technology in education. Quantitative data analysis often involves using statistical software to analyze survey or questionnaire data, such as calculating mean scores and standard deviations and conducting inferential statistics. Qualitative data analysis may involve content or thematic analysis techniques to identify patterns or themes in the data gathered from interviews or focus groups. Finally, the paper discusses the importance of integrating technology into Islamic pesantren education and the need for pesantren institutions to keep pace with technological advancements to prepare their students for the demands of the 21st-century workforce.